2007
DOI: 10.1096/fj.06-6805com
|View full text |Cite
|
Sign up to set email alerts
|

Multiple triggers of cell death in sepsis: death receptor and mitochondrial‐mediated apoptosis

Abstract: Lymphocyte apoptosis plays a central role in the pathophysiology of sepsis. Lymphocyte apoptosis was examined in mice with defective death receptor pathways due to transgenic expression of a dominant negative mutant of Fas-associated death domain (FADD-DN) or Bid-/- and in mice with defective mitochondrial-mediated pathways due to loss of Bim-/-, Puma-/-, or Noxa-/-. FADD-DN transgenic and Bid-/- mice had significant albeit incomplete protection, and this protection was associated with increased survival. Surp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
137
1
6

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 143 publications
(152 citation statements)
references
References 59 publications
8
137
1
6
Order By: Relevance
“…Animal studies have documented the requirement of an intact T cell system to adequately combat a septic challenge (29,37). More recently, animal-based experiments have demonstrated that experimental septic shock is characterized by widespread T cell apoptosis and that preventing T cell apoptosis positively impacts the outcome of experimental sepsis (38)(39)(40)(41)(42)(43)(44)(45). Importantly, the concept of T cell apoptosis in human sepsis has been indirectly corroborated by autopsy studies (36,46).…”
Section: R E S E a R C H A R T I C L E M O L M Ementioning
confidence: 99%
“…Animal studies have documented the requirement of an intact T cell system to adequately combat a septic challenge (29,37). More recently, animal-based experiments have demonstrated that experimental septic shock is characterized by widespread T cell apoptosis and that preventing T cell apoptosis positively impacts the outcome of experimental sepsis (38)(39)(40)(41)(42)(43)(44)(45). Importantly, the concept of T cell apoptosis in human sepsis has been indirectly corroborated by autopsy studies (36,46).…”
Section: R E S E a R C H A R T I C L E M O L M Ementioning
confidence: 99%
“…Both the death-receptor and the mitochondrial pathways are likely to be involved in sepsis-induced apoptosis, as well as numerous inducers including steroids, cytokines (TNF-α, HMGB1), Fas ligand, heat shock proteins, oxygen radicals, nitric oxide, and some specific T lymphocytes (13,120,137,138).…”
Section: Monitoring Of Apoptosismentioning
confidence: 99%
“…Mammalian apoptotic cell death in sepsis proceeds through two distinct pathways, the death receptor pathway and the mitochondrial pathway, that converge to activate caspases, resulting in intracellular demolition (25,26). The extrinsic, or death receptor, pathway is triggered by signaling through TNF, Trail and Fas (19,27,28).…”
Section: Discussionmentioning
confidence: 99%